2013
DOI: 10.1111/jocs.12254
|View full text |Cite
|
Sign up to set email alerts
|

Early Heparin Administration Attenuates Tissue Factor-Mediated Thrombin Generation During Simulated Cardiopulmonary Bypass

Abstract: Heparin-induced TFPI elevation attenuates TF-mediated thrombin generation. Early heparin administration prior to the emergence of plasma TF may represent a novel strategy for controlling thrombin generation by the extrinsic coagulation pathway during CPB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(35 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, in the lack of extrinsic coagulation pathway activation by the surgical field, heparin induces tissue factor pathway inhibitor (TFPI) elevation and attenuates tissue factor-mediated thrombin generation. 19 However, the elevation of C3 indicates the presence of an inflammatory response in agreement with the clinical setting or in vitro findings by others. 20,21 Our findings are in agreement with Pekna et al, who previously suggested that the blood-gas interface during cardiopulmonary bypass induces complement activation and increases in C3.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, in the lack of extrinsic coagulation pathway activation by the surgical field, heparin induces tissue factor pathway inhibitor (TFPI) elevation and attenuates tissue factor-mediated thrombin generation. 19 However, the elevation of C3 indicates the presence of an inflammatory response in agreement with the clinical setting or in vitro findings by others. 20,21 Our findings are in agreement with Pekna et al, who previously suggested that the blood-gas interface during cardiopulmonary bypass induces complement activation and increases in C3.…”
Section: Discussionsupporting
confidence: 87%
“…10,11 Tissue factor-dependent coagulation and inflammation, as a result of monocyte activation and surgical trauma, also occur during CPB. [12][13][14][15] In addition, coagulation proteases can cross-activate other plasma proteolytic cascades and vice versa. 16,17 Thus, the neonate undergoing CPB is susceptible to widespread and unregulated proteolysis with consumption of plasma protease inhibitors that regulate blood coagulation, fibrinolysis, complement and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…TFPI attenuates procoagulant processes by targeting the extrinsic pathway by the inhibition of TF-FVIIa and FXa (37) and it has been previously shown to be significantly correlated with a prolonged TG lag time, and with a reduced ETP and peak height in healthy subjects (38). Additionally, Morizumi et al reported that a heparin-induced elevation of TFPI levels during CPB surgery indeed attenuates TG (39). An elevation of TFPI levels will result in decreased FX activation and increased prothrombinase activity, which is reflected in a reduced maximum rate of prothrombin conversion (19).…”
Section: Discussionmentioning
confidence: 98%